Society, the sacred, and scripture in ancient Judaism : a sociology of knowledge - Lightstone, Jack N. (Studies in Christianity and Judaism ;, 1988)
This work explores the relationship between religion, social patterns, and the perception of the character of scripture in four modes of Ancient Judaism: (1) the Jerusalem community of the fifth to fourth centuries B.C.E. (ie, the Early Second Temple Period); (2) the Judaism of the Graeco-Roman Disapora down to the end of the fourth century of the Christian Era; (3) earliest rabbinic Judaism in the second century C.E> in the land of Israel; (4) Late Antique Talmudic Rabbinism, primarily inn Babylonia, down to the sixth century of the Christian Era. Lightstone attempts not only to describe the.